القصر وأساليبه في اللغة العربية (دراسة بلاغية تحليلية): The Specification (Al-Qasar) and its Styles in Arabic (Analytical rhetorical study) - Nazir Ahmad; Dr. Habeebullah Khan (jihat-ul-islam, 2021)
The specification (Al-Qasar) and its styles have a prominent role in conformity of speech to the situation. It strengthens meaning and increases its effect on the addressee. The researcher started his article by defining the specification lexically and terminologically, and then dealt with the ways of rhetorical use that correspond to the situation, and addressed some of the methods and types of the specification with references from Holy Qur’ān, Al-Ḥadīṯ, Arabic prose and poetry. He noted through it that the Specification is not limited to the Subject and Predicate, but as it is located in them like wires, it is located between both sides of the sentences, then he addressed the difference between the ways of the Specification answering the question: Is it indicative of the Specification by placement or by Tenor and Sense? Explaining with the verses of Holy Qur’ān, Al-Ḥadīṯ, Arabic prose and poetry. At the end of the article the researcher mentioned his findings by writing this article and reading in rhetorical books, classic and modern, and thinking in the verses of the Holy Qur’ān and Al-Ḥadīṯ and in the words of the Arabs.